Nursing and Psychiatry - Trajectory and Evolution: a literature review (Research, Society and Development, 2021)
The present study aimed to discuss the trajectory of nursing care for psychiatric patients, presenting the importance of psychiatric nursing and its changes before and after the psychiatric reform. This is an integrative literature review carried out in the Latin American and Caribbean Literature in Health Sciences databases (LILACS) and in the Medical Literature Analysis and Retrieval Sistem Online (MEDLINE) via the Virtual Health Library (VHL), with use of Health Sciences Descriptors (DECS) in association with the Boolean operator: “Psychiatric reform AND Nursing AND mental health”. 98 documents were found, after inclusion and exclusion criteria, 20 were available, of these, 4 articles fit the theme. The Psychiatric Reform in Nursing ended up bringing great fruits for the future of teaching in this area of activity, in addition to greater monitoring and improvement in teaching patient care. It became evident that the therapeutic relationship between the nursing professional and the therapeutic patient is something mutual and that it was developed through the evolution arising from the Psychiatric Reform, allowing dignified care for these users.